Study of the Synthesis and Properties of Ir(III) Complexes Based on Phosphine Carbonylimide Derivative as Auxiliary Ligand. (30th October 2020) - Guo, Qing‐Mei; Huang, Guo‐Li; Yin, Xin‐Ying; Bian, Jian‐Jian; Li, Xiao‐Mei; Teng, Ming‐Yu
Abstract : Three iridium complexes of (dfppy)2 Ir(DAPB), (dfppy)2 Ir(DAPB), and (dfppy)2 Ir(DAPB) were synthesized by using phosphine carbonylimide derivative as auxiliary ligand and fluoro−/trifluoromethyl substituted 2‐phenylpyridine derivatives as primary ligands. Their quantum efficiency range from 19.4% to 38.5%, and show strong rigidochromic effect. The maximum emission wavelengths of solid‐state fluorescence have remarkable red shifts from 39 to 55 nm compared with these in CH2 Cl2 . Abstract : Three novel iridium(III) complexes which exhibited strong rigidochromic effect with moderate internal quantum efficiencies were synthesized for organic optical functional materials. These complexes could blue‐light‐emitting in solvents and green‐light‐emitting in green.